The "Affirmative Action Hire": Leading Inclusively in Diverse Religious Communities. (March 2016) - Marshall, Joanne M.; Marsh, Tyson E. J.
This case tells the story of a new principal who wants to lead inclusively by including people of all religious and non-religious beliefs. When she questions some of the existing practices in her school, she faces resistance from school members and from the community, who question her identity, her intentions, and her authority. The case is intended for use in leadership courses and highlights some dilemmas of inclusive leadership around religion, as well as those found in the intersectionality of religion, race, and gender.